Review Artikel: Analisis Formulasi dan Evaluasi Tablet Effervescent - Dewi Rahmawati; Dzakiya Zhihrotulwida; M. Fithrul Mubarak; Yani Ambari; Allyssia Salma; Siti Nur Rohmania; Siti Khoiriyah; Achmad Saichoni Arthaganda; Winda Wulandari; Salsabila Firdausi Hernila Putri; Silfi Maslicha (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
The purpose of writing this review article is to analyze the formulation and evaluation of the use of various additives in effervescent tablets. The method used is a literature review taken from journals and other relevant research results regarding the formulation and evaluation of additives in various types of effervescent tablets. The purpose of this analysis is to provide a summary of relevant publications and to improve current understanding in this field. The importance of the formulation and evaluation of additives in effervescent tablets cannot be ignored, because it is a crucial aspect in product development. Decisions in the use of additives must consider the objectives to be achieved, the desired physical characteristics, product stability, and the level of consumer acceptance. With a deep understanding of this formulation and evaluation, we have the potential to produce high-quality effervescent tablets. Variations in additives can also provide different taste and texture characteristics, which of course can affect consumer acceptance.